A study on the differences in the gut microbiota and metabolism between male and female mice in different stress periods - Yajun Qiao; Yajun Qiao; Yajun Qiao; Juan Guo; Qi Xiao; Jianv Wang; Jianv Wang; Xingfang Zhang; Xingfang Zhang; Xinxin Liang; Xinxin Liang; Lixin Wei; et al. (Experimental Biology and Medicine)
The sex difference in depression has long been an unsolved issue. Women are twice as likely to suffer from depression as men. However, there were significant differences in the composition of gut microbiota between women and men. There is a lack of studies linking sex differences in depression to microbiota, and the specific mechanisms of this process have not been explained in detail. The main purpose of this study was to explore the gender differences in the intestinal tract of male and female depressed mice. In this study, chronic restraint stress (CRS) mouse models were used to simulate chronic stress, and behavioral tests were conducted, including the open field test (OFT), tail suspension test (TST) and forced swimming test (FST). Microbial diversity analysis and metabolomics were performed on collected mouse feces. The results showed that female mice were highly active and prone to anxious behavior before stress, and the levels of f-Rikenellaceae, f-Ruminococcaceae and 16α-hydroxyestrone were significantly different from those in male mice. After 21 days (Days) of stress, female mice showed depression-like behavior, and the levels of f-Erysipelotrichaceae, 5α-pregnane-3,20-dione, and 2-hydroxyestradiol were significantly different from those in male mice. After 14 days of stress withdrawal, the depression-like behavior continued to worsen in female mice, and the levels of 5α-pregnane-3,20-dione, estrone glucuronide and f-Erysipelotrichaceae were significantly different from those in male mice. In summary, female mice have stronger stress sensitivity and weaker resilience than male mice, which may be related to differences in bacterial diversity and estrogen metabolism disorders.